A case of Shewanella algae endocarditis: an emerging pathogen with a diverse clinical spectrum. (6th January 2018) - Davidson, Natalie Lousie; Subedi, Shradha; Wilks, Kathryn; Morgan, Joanna
Abstract : Shewanella algae is a rare pathogen related to water exposure in temperate climates. It is commonly associated with skin and soft tissue infections, peritonitis and bacteraemia. We report the first-ever case of S. algae infective endocarditis in a patient with previous splenectomy and explore the difficulties in treatment as well as highlight the importance of this organism as an emerging pathogen.